2017
DOI: 10.4103/0366-6999.208234
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Good's Syndrome in China

Abstract: Background:Good's syndrome (GS) is a rare disease characterized by thymoma, hypogammaglobulinemia, low or absent B-cells, decreased T-cells, an inverted CD4+/CD8+ T-cell ratio and reduced T-cell mitogen proliferative responses. GS is difficult to diagnose preoperatively due to its rarity and lack of typical symptoms, the characteristics of Chinese GS patients are still lacking. This study aimed to systematically review all the clinical, laboratory, and immunologic findings of reported cases of Chinese patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…Since the original description by Dr Robert Good more than 60 years ago, most publications of Good’s syndrome are single case reports or small case series, the previous largest being a systematic review of 47 Chinese patients , and a compilation of 152 cases from cases published prior to 2010 . The aim of our survey was to review the clinical and laboratory features of patients with Good’s syndrome identified through the UK‐PIN immunodeficiency registry and investigate what factors may be associated with specific complications and outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Since the original description by Dr Robert Good more than 60 years ago, most publications of Good’s syndrome are single case reports or small case series, the previous largest being a systematic review of 47 Chinese patients , and a compilation of 152 cases from cases published prior to 2010 . The aim of our survey was to review the clinical and laboratory features of patients with Good’s syndrome identified through the UK‐PIN immunodeficiency registry and investigate what factors may be associated with specific complications and outcome.…”
Section: Introductionmentioning
confidence: 99%
“…GS, a subtype of thymoma firstly described in 1954 by Dr. Good [ 1 ], was a rare disease accompanied by respiratory system abnormality with recurrent bronchitis, sinusitis, pneumonia, and chronic diarrhea. To date, patients diagnosed with GS mainly distributed in Europe and America and totally 47 cases emerged in China [ 2 ]. GS is typically detected based on a diagnosis of thymoma in combination with characteristic clinical laboratory test results, such as a low number or even absence of peripheral B cells, hypogammaglobulinemia, CD4 + T lymphopenia, and an inverted ratio of CD4 + /CD8 + cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thymomas are commonly associated with parathymic syndromes,[ 7 8 9 ] one of the most common is myasthenia gravis (MG). In general, thymic tumors occur in approximately 20–30% of patients with MG and, in turn, MG occurs in 15–60% of patients with thymoma according to different reports.…”
Section: Introductionmentioning
confidence: 99%
“…In general, thymic tumors occur in approximately 20–30% of patients with MG and, in turn, MG occurs in 15–60% of patients with thymoma according to different reports. [ 9 10 11 ] The presence of MG gives thymomas some special pathological and clinical characteristics and may influence its prognosis. [ 12 13 ] Adjuvant radiation therapy was suggested; however, there were still a lot of controversy.…”
Section: Introductionmentioning
confidence: 99%